Pesan Kesehatan Reproduksi Remaja Pada Majalah Gadis - Dewa Ayu Putu Mariana Kencanawati (JURNAL INFO KESEHATAN, 2017)
The development of mass media today is so rapid. One of the mass media that still existed in the hearts of readers until now is teen magazines. Teen magazines that still have high oplag is gadi. Girl magazine presents various information that teenagers need including reproductive health and sexuality. However, although adolescent magazines present a wealth of information about health, adolescent knowledge about pro-profits remains low, this is evidenced by the high rates of unintended pregnancies, IMS and HIV / AIDS that begin to infect teenagers. Therefore, this study aims to find out what messages about reproductive health contained in the magazine girl during the period 2006-2012. This research is descriptive research by using ethnographic content analysis approach, the sample in this research is a magazine of girl which contains a message of reproduction health and sexuality during period 2006-2012 as much 72 copies. The results of the study found that there were 43 articles in girl magazines that contained reproductive health messages, as well as messages published about myths related to kespro, puberty, menstruation, and teenage pregnancy. In conclusion, of 43 articles on reproductive health in magazine girls still, have not provided a source and reference to the article.